Low Potential Heat Recovery Using Heat Pumps - Sorinel TOFAN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2012)
This paper presents a study on the possibility of recovering low thermal potential heat from the cooling technological water of industrial processes. The analysed solution consists in the use of a heat pump which would send the recovered heat to a hot water flow. We started from a technological water flow which was taken over by a 350 m3/h cooling tower and we determined the performances of a heat pump when using various refrigeration agents, for a range of values of the temperature of hot water and the temperature of the return of technological water which varies according to season.